2022
DOI: 10.1186/s41043-021-00273-8
|View full text |Cite
|
Sign up to set email alerts
|

Socio-biomedical predictors of child nutrition in India: an ecological analysis from a nationally representative Demographic and Health Survey, 2015–2016

Abstract: Background Despite significant economic growth and development, undernutrition among children remains a major public health challenge for low- and middle-income countries in the twenty-first century. In Millennium Development Goals, India committed halving the prevalence of underweight children by 2015. This study aimed to explain the geographical variation in child malnutrition level and understand the socio-biomedical predictors of child nutrition in India. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…29 Negative correlation has been found between the availability of food, exclusive breast feeding status, and wasting among children. 30 Food availability differs across the states and so does the nutrition status of children. The Indian State Hunger Index (ISHI) 2009 estimated food insecurity across 17 major states of India and found that 12 of the states fell in the "alarming" category and one state, that is, Madhya Pradesh fell into the "extremely alarming" category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Negative correlation has been found between the availability of food, exclusive breast feeding status, and wasting among children. 30 Food availability differs across the states and so does the nutrition status of children. The Indian State Hunger Index (ISHI) 2009 estimated food insecurity across 17 major states of India and found that 12 of the states fell in the "alarming" category and one state, that is, Madhya Pradesh fell into the "extremely alarming" category.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in the African region also discusses the association between variation in season and the wasting prevalence among children 29 . Negative correlation has been found between the availability of food, exclusive breast feeding status, and wasting among children 30 . Food availability differs across the states and so does the nutrition status of children.…”
Section: Discussionmentioning
confidence: 99%